TIPOLOGI DAERAH ALIRAN SUNGAI UNTUK MITIGASI BENCANA BANJIR DI DAERAH ALIRAN SUNGAI MUSI - Irfan Budi Pramono; Pamungkas Buana Putra (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2017)
The cause of flood problems could be identified from problems that happened in the catchment area as flood water discharge and flooded or inundation area. The objective of this study is to identify the degree of flood vulnerability, both flood water discharge and flooded area, as a basis of flood mitigation at the Musi Watershed. Method applied on this study is the watershed typology formula developed by Watershed Management Technology Centre (WMTC) for identifying flood vulnerability based on land system, land cover, and maximum daily rainfall. Degree of flood vulnerability is differentiated into five categories. Musi Watershed was divided into 14 sub watersheds and each sub watershed is identified its degree of vulnerability on flood water discharge and area of flooded area. Based on these values the rank of sub watershed to its degree of degradation could be generated. The result showed that Komering and Deras Sub Watersheds were vulnerable to flood due to their nature. Ogan and Upper Musi Sub watersheds were the source of flood due to different caused by high rainfall, while Upper Musi was generated by high land vulnerable. The mitigation program in the flood prone area is complicated since Deras Sub Watershed was the accumulation of many downstream sub watersheds. Mitigation program in the discharge area could be done in Upper Musi Sub Watershed, since it has the highest vulnerability. Upper Musi is also the upstream of Deras Sub Watershed.